2018
DOI: 10.12944/crnfsj.6.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Fats Declaration, Awareness and Consumption in Saudi Arabia

Abstract: Hydrogenatedoil(HO) has been considered one of the major sources of artificial trans-fats that is associated with various public health problems. In the present work, a cross-sectional survey was conducted tomonitortrans- fats recording approaches in some food package(N=181) collected from some Saudi markets, 2014-2016. Assessment of participants awareness of HO and consumption frequencies of selected products that listed trans-fats in their package were also conducted based on interview questionnaires (N=302)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…According to an unpublished study conducted by our team, 32% only of the products available in the Lebanese markets reported IP-TFAs on their labels (data not shown). Our finding came to hand in hand with Kamel et al ( 67 ), in which 181 food products were sampled from local supermarkets in Saudi Arabia and showed that one-third of the products mentioned IP-TFAs on the nutrition label. Moreover, while the majority of the investigated samples in our project had low levels of IP-TFAs, up to 14 g of TFAs per 100 g of food was observed in certain oils and fats sold at the Lebanese markets.…”
Section: Discussionsupporting
confidence: 73%
“…According to an unpublished study conducted by our team, 32% only of the products available in the Lebanese markets reported IP-TFAs on their labels (data not shown). Our finding came to hand in hand with Kamel et al ( 67 ), in which 181 food products were sampled from local supermarkets in Saudi Arabia and showed that one-third of the products mentioned IP-TFAs on the nutrition label. Moreover, while the majority of the investigated samples in our project had low levels of IP-TFAs, up to 14 g of TFAs per 100 g of food was observed in certain oils and fats sold at the Lebanese markets.…”
Section: Discussionsupporting
confidence: 73%
“…According to an unpublished study conducted by our team, 32% only of the products available in the Lebanese markets reported TFAs on their labels (Data not shown). Our finding came to hand by hand with Kamel et al [40], in which 181 food products were sampled from local supermarkets in Saudi Arabia and showed that one-third of the products mentioned TFAs on the nutrition label. Moreover, while the majority of the investigated samples in our project had low levels of TFAs, up to 14 g of TFAs per 100 g of food was observed in certain oils and fats sold at the Lebanese markets.…”
Section: Comparison Between Lebanese Market Basket Investigation and Other Global And Regional Market Investigationssupporting
confidence: 57%
“…Assessment of TFA Levels in Food and TFA-Related KAB Several countries in the EMR (9/22 countries; 41%), including Egypt, Iran, Jordan, Kingdom of Saudi Arabia (KSA), Kuwait, Lebanon, Morocco, Pakistan, and Tunisia, have evaluated TFA levels in local foods and commodities (Supplementary Table 3) (14,39,49,. The majority of available TFA content data were derived based on chemical analysis of food products (39, 49, 52-56, 58, 60-70, 72-74, 77, 79-97), while very few studies have collected TFA content data based on food labels and packages (55,75,76). Most of the available studies have reported very high levels in fast foods (fried meats, sausages, French fries), pastries, potato chips, biscuits, wafers, cakes, donuts, chocolates, traditional sweets, as well as dairy products (milk, cream, cheeses).…”
Section: Assessment Of Tfa Intakementioning
confidence: 99%